Effect of the extent of posterior septectomy on surgical access during the endoscopic endonasal approach to the sella: A technical note - Reem Elwy; Abdel Rahman Younes; Amr K. Elsamman (Brain and Spine)
Background: Using the bi-nostril 4-hand technique during the endoscopic endonasal approach (EEA) facilitates bimanual microsurgical techniques yet requires resection of the posterior nasal septum. The surgical exposure and degree of maneuverability gained proportionate to the extent of posterior septectomy in the sagittal plane was previously quantified. Research question: We aim to describe our technique of posterior septectomy, and the effect of its extent in the axial plane on surgical access, and instrument maneuverability. Material and methods: After fracturing the posterosuperior nasal septum, we disarticulate the vomer from the sphenoid rostrum and remove its upper part. The sphenoid rostrum is excised next exposing the clival recess where a suction tip without a side channel is anchored, allowing the assisting surgeon to use an additional instrument in their dominant hand. The vomer is removed down to the level of the floor of the sphenoid sinus. Results: A wide exposure is achieved in the coronal plane bilaterally at the level of the sphenoid rostrum allowing unobstructed instrument manipulation in the craniocaudal and cross-court trajectories. Furthermore, the floor of the sella is reached through a straight rather than angled trajectory facilitating surgical access, manipulation, and instrument maneuverability. For lateral lesions requiring contralateral access, the assisting surgeon can assist in dissection from the contralateral nostril without changing the position of the endoscope. Discussion and conclusion: Removing the upper vomer improves surgical access, and instrument maneuverability. Simultaneous dissection from both nostrils might be attempted. Caudally extending the posterior septectomy during the EEA allows better exposure and improves surgical access in all planes.